2023
DOI: 10.1038/s41467-023-39370-z
|View full text |Cite|
|
Sign up to set email alerts
|

Personalized aerosolised bacteriophage treatment of a chronic lung infection due to multidrug-resistant Pseudomonas aeruginosa

Thilo Köhler,
Alexandre Luscher,
Léna Falconnet
et al.

Abstract: Bacteriophage therapy has been suggested as an alternative or complementary strategy for the treatment of multidrug resistant (MDR) bacterial infections. Here, we report the favourable clinical evolution of a 41-year-old male patient with a Kartagener syndrome complicated by a life-threatening chronic MDR Pseudomonas aeruginosa infection, who is treated successfully with iterative aerosolized phage treatments specifically directed against the patient’s isolate. We follow the longitudinal evolution of both phag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…LPS-5 is a lytic phage that infects Pa . It is a member of the Pakpunavirus family and uses pseudomonal lipopolysaccharide (LPS) for viral entry 14 . A representative transmission electron microscopy image of LPS-5 and representative lytic plaque morphology on Pseudomonas aeruginosa PAO1 are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…LPS-5 is a lytic phage that infects Pa . It is a member of the Pakpunavirus family and uses pseudomonal lipopolysaccharide (LPS) for viral entry 14 . A representative transmission electron microscopy image of LPS-5 and representative lytic plaque morphology on Pseudomonas aeruginosa PAO1 are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Lytic bacteriophages (phages), viruses that kill bacteria, are an exciting treatment option for AMR bacterial infections [7][8][9][10] . Multiple studies have demonstrated the efficacy of phage therapy against MDR Pa [11][12][13][14] , either alone or in conjunction with conventional antibiotics 15 . Phage therapy is saving lives; however, success has been inconsistent [16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, in a lysogenic cycle, incorporation of viral DNA into host DNA occurs . Bacteriophages tend to be specific in terms of the receptors they interact with and the species they can affect/target. , Advantages associated with bacteriophage therapy include effectiveness against MDR bacteria, , specificity in terms of species and/or strains, and leaving the patient’s gut microbiome largely unaltered. , Furthermore, bacteriophage therapy has been shown to have an excellent safety profile in human beings. , All of these features mean that as the threat of MDR strains becomes more imminent, bacteriophage therapy has seen a promising resurgence in interest. In a recent study, a group of researchers designed and administered personalized bacteriophage therapy to an individual suffering from lung infection caused by MDR P. aeruginosa and appeared to be successful in stopping antibiotic therapy completely . Other instances of successful personalized bacteriophage therapy against MDR strains have also been reported .…”
Section: Antibioticsmentioning
confidence: 99%
“… 308 , 310 312 All of these features mean that as the threat of MDR strains becomes more imminent, bacteriophage therapy has seen a promising resurgence in interest. 313 316 In a recent study, a group of researchers designed and administered personalized bacteriophage therapy to an individual suffering from lung infection caused by MDR P. aeruginosa and appeared to be successful in stopping antibiotic therapy completely. 316 Other instances of successful personalized bacteriophage therapy against MDR strains have also been reported.…”
Section: Antibioticsmentioning
confidence: 99%
“…Studies in this general direction have been conducted for (1) stabilizing phages for aerosol delivery [60,61], (2) freeze drying, and (3) in-air spray drying [62][63][64][65]. Spray drying is closest to what happens in the environment.…”
Section: The Potential Future Of Dry Phage Therapy Cocktails: An Impr...mentioning
confidence: 99%